From recognition to expression: extending cardiovascular emotional dampening to facial expressions under elevated blood pressure - Bhowmick, Shatabdi; Shukla, Meenakshi; Pandey, Rakesh (Frontiers in Psychiatry, 2025)
IntroductionCardiovascular Emotional Dampening (CED) refers to blunted emotional responsiveness in individuals with elevated blood pressure (BP), but research has exclusively focused on how such individuals perceive others’ emotions. Given evidence that the ability to produce facial expressions of emotions is closely tied to emotion recognition via shared neural mechanisms, examining expressive deficits in CED could reveal additional pathways linking elevated BP with emotional communication. This study examined whether individuals with higher systolic and diastolic BP exhibit reduced accuracy and intensity when generating prototypical facial expressions of emotion.MethodsParticipants (N = 74) across normotensive (n=33), prehypertensive (n=21), and hypertensive (n=20) categories were instructed to pose six basic emotions. Facial Action Units (AUs) were coded using certified human coders and OpenFace, allowing comparison of AU intensities, human-machine agreement, and expression accuracy. Prototypical emotion templates were used to determine accuracy, and interrater agreement was quantified via five complementary indices.ResultsEmotional expression accuracy was significantly lower in prehypertensive and hypertensive groups, particularly for sadness, fear, and surprise. Correlational analyses revealed significant negative associations of SBP and DBP with accuracy of expressing sadness, disgust, and anger. Notably, expressions of happiness were preserved. Although overall agreement between human and machine ratings was high, reduced intensity and increased AU sparsity at higher BP levels likely suppressed reliability metrics.DiscussionThese findings extend the CED framework from recognition to expression, revealing that elevated BP may blunt the expressive channel for particularly negative emotions, irrespective of arousal level. Though facial expression of emotions is limited to negative emotions, it is generalized across different levels of arousal within this category - from low (sad), moderate (disgust), to high (anger).The pattern suggests central autonomic influences on facial expressivity of emotions and opens new directions for identifying emotional communication deficits in at risk populations.